Rastreabilidade da cama de aviário por isótopos estáveis em bovinos leiteiros - Carvalho, Marco Antônio Gonzales de [UNESP] (2015)
Traceability of poultry litter in dairy cow diet was performed by analysis of stable isotopes of carbon (δ13C), nitrogen (δ15N), oxygen (δ18O) and deuterium (δ2H) in milk and its fractions (fat, whey, and protein). The values of δ13C and δ15N were higher in milk and fractions of animals fed diet containing poultry litter than those fed with vegetable diet, while the values of δ18O and δ2H remained similar. The principal component analysis of milk and fractions (protein and water) differed among the group which diet contained poultry litter from those fed vegetable diet, where the stable isotopes of carbon and nitrogen were more representative. However, by stable isotopes in the fat was not possible to differentiate between treatments. The results demonstrate the capacity to track the presence of poultry litter in dairy cow diet by isotopic analysis of milk and its components (protein and whey), emerging as a new tool in the supervision and quality control of this food